Recontextualizing Ki Hajar Dewantara’s Educational Philosophy in the Era of Merdeka Belajar and Global Disruption - Ismaiza Busti; Refinal; Saifullah SA; Desi Asmaret; Julhadi; Usman Aliyu Yunusa (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: To critically analyze Ki Hajar Dewantara's educational philosophy and its relevance to contemporary Indonesian education, especially in the context of the "Freedom of Learning" policy. Theoretical framework: This research is based on the theoretical framework of humanistic, cultural, and liberation education, with an emphasis on student autonomy, moral development, and the formation of national identity. The triadic philosophy of Ki Hajar Dewantara, which consists of the principles of Ing Ngarsa Sung Tulada, Ing Madya Mangun Karsa, and Tut Wuri Handayani, is used as a conceptual basis in this study. Literature review: A literature review shows that although Ki Hajar's educational values are often referenced, there are still shortcomings in integrative and practical studies that relate his thinking to the demands of modern education, especially in the era of digital transformation, global competition, and curriculum reform. Most studies are historical or philosophical, without providing a concrete operational framework for educators and policymakers. Methods: This qualitative research uses historical, sociocultural, and content analysis approaches. Primary data was obtained from Ki Hajar Dewantara's original writings, speeches, and policy documents. Secondary data includes related literature and contemporary educational frameworks such as the Independent Curriculum. The analysis was carried out through thematic categorization and interpretive synthesis. Result: The results of the study show that Ki Hajar Dewantara's thinking remains relevant, especially in terms of educational freedom, cultural roots, and moral character development. His thinking became the philosophical basis for rehumanizing education in the dominance of metrics and standardization. However, reinterpretation is needed to be in line with the digital learning environment and 21st-century competencies. Implications: National education policies need to integrate local cultural values and humanistic pedagogical approaches to create sustainable, identity-based learning. Novelty: The uniqueness of this research lies in the reactualization of Ki Hajar Dewantara's educational philosophy as a contextual and adaptive living paradigm to current and future educational challenges.